THE LAW OF RIGHT TO PRIVACY IN INDIA: PROTECTING PRIVACY IN THE DIGITAL ERA: CHALLENGES - Grover, Davesh; Singh, Ramveer (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The digital revolution has transformed India's socio-economic landscape but also compromised citizens' right to privacy. This research examines the challenges and vulnerabilities in India's existing legal framework, markedly in the perspective of digital technologies. It analyzes the constitutional and statutory provisions, judicial decisions, and international human rights instruments to identify gaps and propose reforms. This research aims to address these concerns by examining the challenges and vulnerabilities in India's existing legal framework, specifically from the perspective of digital technologies. The study will analyze constitutional and statutory provisions, judicial decisions, and international human rights instruments to identify gaps and propose reforms. The rapid growth of digital technologies in India has led to a critical need for robust digital privacy protections. This research undertakes a comprehensive examination of the challenges and vulnerabilities in India's existing legal framework, highlighting the gaps and inconsistencies that compromise citizens' right to privacy. By analyzing constitutional and statutory provisions, judicial decisions, and international human rights instruments, this study identifies key areas for reform and proposes concrete recommendations to strengthen India's digital privacy landscape. The objective is to strengthen India's privacy laws, ensuring citizens' digital privacy is safeguarded. By finding areas for improvement and recommending reforms, this research contributes to the ongoing debate on privacy in India. This research endeavors to inform policy reforms and corrective actions, enhancing the protection of citizens' digital privacy in India